Integrability and Multiple Limit Cycles in a Predator-Prey System with Fear Effect. (27th June 2019) - Li, Xinli; Zhang, Ming
Abstract : In this paper, a class of predator-prey systems with fear effect is investigated, the integrability conditions of the origin and the positive equilibrium are obtained, and the fact that three limit cycles can be bifurcated from the positive equilibrium is proved, so bistable phenomenon can occur for this system.